Utilization of Open Reasoned Multiple Choice Test in Analyzing Misconceptions about The Respiratory System Material for Second Grade (XI Class) of Senior High School - Rambe, Sari Putri; Ulfa, Syarifah Widya (Universitas Labuhanbatu, 2022)
The reason for this study was to dissect understudies misguided judgments by utilizing the Multiple Choice Test Â with open reasons and to describe the causes of misconceptions in the respiratory system material for third class (XI) at SMA Negeri 2 Rantau Selatan with a sample of 62 students. This study uses quantitative research with descriptive methods to obtain information and data that can be processed to find out how big the level of misconceptions that occurs in students. The instruments used are multiple choice questions with open reasons and interviews. The data acquired will be introduced as numbers and afterward investigated utilizing by Microsoft Excel 2007, then perform calculations using the formula proposed by Arikunto to determine the level of understudies who figure out ideas, don't grasp ideas and misguided judgments. The results showed that 28.3992% of students understood concepts, 39.086% of students knew concepts, and 32.1505% of students experienced misconceptions on the respiratory system material. Factors causing misconceptions, namely, (1) students experience a lot of lack concentration and lack of interest to reading the material studied during learning, (2) some sub-materials make students still feel confused about the mechanisms of breathing, transport and gas exchange, (3) the teacher's book and students only use by Erlangga publisher package from school provides and, (4) the teaching method of teacher does not routinely carry out practicum, because the condition equipment of laboratory room not support to used